2012
DOI: 10.4269/ajtmh.2012.11-0503
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Assay for Species Identification and Monitoring of Insecticide Resistance in Anopheles punctulatus Group Populations of Papua New Guinea

Abstract: Abstract. Anopheles punctulatus sibling species ( An. punctulatus s.s., Anopheles koliensis , and Anopheles farauti species complex [eight cryptic species]) are principal vectors of malaria and filariasis in the Southwest Pacific. Given significant effort to reduce malaria and filariasis transmission through insecticide-treated net distribution in the region, effective strategies to monitor evolution of insecticide resistance among An . punctulatus sibling species is essential. Mutations in the voltage-gated s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 70 publications
1
13
0
Order By: Relevance
“…() observed that T . infestans‐ resistant populations from Gran Chaco (ecoregion covering part of Argentina, Bolivia and Paraguay) have the kdr mutation at similar frequencies but have very different resistance ratios (Henry‐Halldin et al ., ). These data suggest that other mechanisms could be involved in triatomine insecticide resistance.…”
Section: Discussionmentioning
confidence: 97%
“…() observed that T . infestans‐ resistant populations from Gran Chaco (ecoregion covering part of Argentina, Bolivia and Paraguay) have the kdr mutation at similar frequencies but have very different resistance ratios (Henry‐Halldin et al ., ). These data suggest that other mechanisms could be involved in triatomine insecticide resistance.…”
Section: Discussionmentioning
confidence: 97%
“…For example, control of malaria by releasing genetically modified-, sterile-, male mosquitoes as was recently proposed [59] would require, in PNG, independent engineering of mosquitoes from, at least, five highly divergent species to significantly impact the populations of the main malaria vectors. In addition, if AP sibling species are reproductively isolated from each other, insecticide resistance arising in one species is unlikely to spread quickly across all AP mosquitoes, but instead resistance mutations would have to occur independently in each species [29]. Further investigations are required to definitively rule out the existence of gene flow among most AP sibling species, as well as to confirm the observation of putative mt genome introgression between An .…”
Section: Discussionmentioning
confidence: 99%
“…farauti 4 - have been described as competent vectors of malaria [23,24]. Phylogenetic studies of this group have focused on DNA sequences of ribosomal RNAs [25,26], mitochondrial genes [27,28], ribosomal ITS2 [19], and voltage-gated sodium channel gene [29]. However, the genetic information generated in these studies has not allowed robust determination of the AP group phylogeny and has often yielded conflicting results [19,27].…”
Section: Introductionmentioning
confidence: 99%
“…punctulatus mosquitoes have shown limited fine‐scale population stratification in mainland PNG (Henry‐Halldin et al . ; Logue et al . ; Seah et al .…”
Section: Discussionmentioning
confidence: 99%
“…Wild‐caught mosquitoes were collected in the Madang province by the Entomology unit of the Papua New Guinea Institute of Medical Research (PNGIMR) as previously described (Henry‐Halldin et al . , ). We extracted genomic DNA from individual mosquitoes with DNeasy blood and tissue kits (Qiagen ® ) according to the supplemental protocol for purification of insect DNA with one modification: each mosquito was initially placed in a 2 mL tube with one 5‐mm steel bead and 180 μL of PBS and homogenized by high‐speed shaking at 15 Hz for 90 s with a Qiagen TissueLyser II instrument.…”
Section: Methodsmentioning
confidence: 99%